2012
DOI: 10.1371/journal.pone.0039416
|View full text |Cite
|
Sign up to set email alerts
|

Human Peripheral Blood Mononuclear Cells Exhibit Heterogeneous CD52 Expression Levels and Show Differential Sensitivity to Alemtuzumab Mediated Cytolysis

Abstract: Alemtuzumab is a monoclonal antibody that targets cell surface CD52 and is effective in depleting lymphocytes by cytolytic effects in vivo. Although the cytolytic effects of alemtuzumab are dependent on the density of CD52 antigen on cells, there is scant information regarding the expression levels of CD52 on different cell types. In this study, CD52 expression was assessed on phenotypically distinct subsets of lymphoid and myeloid cells in peripheral blood mononuclear cells (PBMCs) from normal donors. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
140
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(149 citation statements)
references
References 44 publications
4
140
3
Order By: Relevance
“…In one study, it was reported that the rate of apoptosis was reduced in an allele dose-dependent manner. 4 Although we did not find this to be the case with the donors in our study, there was some suggestion, from the functional studies, that an allele dose effect may be present in some cellular subsets (for example, NKT cells). Additionally, where both the patient and the donor had an 'apoptosis-resistant' genotype the OS was significantly worse, suggesting that assessment for the presence of multiple deletions may be relevant.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…In one study, it was reported that the rate of apoptosis was reduced in an allele dose-dependent manner. 4 Although we did not find this to be the case with the donors in our study, there was some suggestion, from the functional studies, that an allele dose effect may be present in some cellular subsets (for example, NKT cells). Additionally, where both the patient and the donor had an 'apoptosis-resistant' genotype the OS was significantly worse, suggesting that assessment for the presence of multiple deletions may be relevant.…”
Section: Discussioncontrasting
confidence: 71%
“…The development of GVHD, and a subsequently increased TRM rate remains a major impediment to transplant success. 1 The anti-CD52 monoclonal Ab Campath-1H (Alemtuzumab) effectively depletes T lymphocytes and Agpresenting cells [2][3][4] and reduces the risk of both acute (aGVHD) and chronic GVHD (cGVHD). 5,6 There are three main pathways that have been established in Alemtuzumab-mediated cell death: complement-dependent cytotoxicity, 7,8 Ab-dependent cell mediated cytotoxicity 9,10 and apoptosis (activation induced cell death, AICD).…”
Section: Introductionmentioning
confidence: 99%
“…Anti-CD52 mAb treatment has been studied during the past years as one of the medications with the longest lasting effect against multiple sclerosis (MS) (7). It depletes T and B lymphocytes and, to a lesser extent, monocytes, macrophages, dendritic cells, and NK cells via Ab-dependent cellular cytotoxicity, complement-induced cell lysis (8)(9)(10)(11), and the induction of apoptosis (12). Although effectively depleting all CD52-bearing cells, this immunodepleting therapy does not affect hematopoietic stem cells (13), and thus the potential for an immune response reconstitution is preserved.…”
mentioning
confidence: 99%
“…54 Since alemtuzumab may strongly deplete the number of T-cells, it has been used to reduce the risk of GVHD in patients undergoing allo-HSCT. In ATL cells, more than 90% of tumor cells strongly express CD52.…”
Section: Alemtuzumabmentioning
confidence: 99%